Community Economic Empowerment Based on Ecotourism from a Sharia Economic Perspective: A Study on Mada Oi Tampuro, Piong Village - Lasmi; Muhammad Rasyad Al Fajar; Muhammad Zia Ulhaq (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to identify empowerment models, analyze income distribution patterns, and validate the alignment of ecotourism management practices in Mada Oi Tampuro, Piong Village, with sharia economic principles. Using a descriptive qualitative approach, this study was conducted through data collection from 15 informants using interview, observation, and documentation techniques. The results of the study indicate that ecotourism has succeeded in providing a multiplier effect that increases the income of micro-entrepreneurs as a form of hifdz al-maal . However, there are obstacles in the form of the application of ta'awun values that are still limited to technical functions and the uneven distribution of benefits that violate the principle of distributive justice ( 'adl ). Overall, the sustainability of this ecotourism requires restructuring of ticket and parking management through the formalization of mudharabah or syirkah inan contracts , as well as optimizing the role of the village government as ulil amri to realize holistic maslahah.